2013
DOI: 10.1007/s11255-013-0378-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to nephrotic-range proteinuria in late-stage chronic kidney disease patients with diabetes mellitus

Abstract: Higher systolic blood pressure, serum phosphorus, and triglyceride levels are associated with nephrotic-range proteinuria in patients with diabetic nephropathy and CKD stage 3-5. Further studies should clarify whether a reduction in serum phosphorus would lead to a decrease in proteinuria in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…This is probably because the number of patients included in this study was relatively small. Recently, even mild elevation of systolic blood pressure beyond 121 mmHg was shown to be strongly associated with nephrotic range proteinuria in diabetic patients with severely impaired renal function [22]. Furthermore, a previous study has shown that aggressive antihypertensive treatment could lead to remission of nephrotic range proteinuria and slowed down the progression of nephropathy [10].…”
Section: Discussionmentioning
confidence: 99%
“…This is probably because the number of patients included in this study was relatively small. Recently, even mild elevation of systolic blood pressure beyond 121 mmHg was shown to be strongly associated with nephrotic range proteinuria in diabetic patients with severely impaired renal function [22]. Furthermore, a previous study has shown that aggressive antihypertensive treatment could lead to remission of nephrotic range proteinuria and slowed down the progression of nephropathy [10].…”
Section: Discussionmentioning
confidence: 99%